Diagnóstico del reflujo fémoro-safeno: Comparación de 5 métodos de estudio con los hallazgos intraoperatorios - Rudnitzky, Omar; Sciuto, Fernando; Davezac, Víctor; Caputti, Sonia (Cirugía del Uruguay, 1991)
The diagnosis of femoro-saphenous reflux is of utmost importance for the corree/ treatment of Chronic Venous Failure patients. The authors evaluated the diagnostic accuracy of the climc, Doppler, Ouplex, ascending and descending phlebography in 53 patients that were tested intraoperatively for FSR. They point out /he low sensitivity of the c/inic (53%) and the high sensitivity and specificity of Duplex (100%) and Doppler (98 and 100%) considerably greater than ascending phlebography (78 and 75%), until now known as the classical paraclinical method.